Tetrabutylammonium Iodide (TBAI) Catalyzed Electrochemical C–H Bond Activation of 2-Arylated N-Methoxyamides for the Synthesis of Phenanthridinones - Subramanian, Kripa; Yedage, Subhash L.; Sethi, Kashish; Bhanage, Bhalchandra M. (Synlett, 2021)
An electrochemical method for the synthesis of phenanthridinones through constant-potential electrolysis (CPE) mediated by Bu4NI (TBAI) is reported. The protocol is metal and oxidant free, and proceeds with 100% current efficiency. TBAI plays a dual role as both a redox catalyst and a supporting electrolyte. The intramolecular C–H activation proceeds under mild reaction conditions and with a short reaction time through electrochemically generated amidyl radicals. The reaction has been scaled up to a gram level, showing its practicability, and the synthetic utility and applicability of the protocol have been demonstrated by a direct one-step synthesis of the bioactive compound phenaglaydon.
Keywords: tetrabutylammonium iodide; phenanthridinones; amidyl radicals; electrochemistry; C–H bond activation; constant-potential electrolysis